Editorial - Melba Libia Cárdenas; María Claudia Nieto Cruz (Profile: Issues in Teachers' Professional Development)
To start, the exercise of writing is a difficult task. Nothing more challenging than the whiteness of an empty page. Whether the writing outcome is a personal product or a piece to be socialized in the academic world, the writing task demands a lot from the ones that succumb by pleasure or obligation to the writing assignment. Apart from the skill of writing, authors of articles published in academic journals are obliged to stick to the specific publication’s parameters. Strict datelines, number of words and specific sections to be included will shape the writer’s production. The resulting texts in most of the circumstances will fit the publications’ guidelines but may, in turn, restrict the writer’s flow and line of thought. Authors may be restricted by limitations but if they want to publish they should stick to the parameters of the target publication. In other words, stick and publish or ignore and be ignored.